Idiopathic, Serial Coronary Vessels Dissection in a Young Woman with Psychological Stress: A Case Report and Review of the Literature - Alessio Arrivi; Caterina Milici; Carlo Bock; Attilio Placanica; Enrico Boschetti; Marcello Dominici (Case Reports in Vascular Medicine)
Spontaneous coronary artery dissection (SCAD) is a very rare disease, associated with high mortality rate, whose etiology and pathogenesis are poorly understood. Its sporadic nature and the varied angiographic extent make firm recommendations regarding revascularization impossible. The case described is that of a young, otherwise healthy woman, without a known underlying condition which may lead to SCAD, but with a history of intense psychological stress. We managed the patient with a conservative approach based on watchful waiting, medical therapy, and plain old balloon angioplasty (POBA) with low inflation atmospheres.